Ukraine : Ex Post Evaluation of Exceptional Access Under the 2010 Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Ukraine's Ex Post Evaluation of Exceptional Access Under the 2010 Stand-By Arrangement. For the most part, the 2010 program was appropriately designed given the ambitious agenda it had set out to accomplish. The macroeconomic strategy and program design correctly addressed the most important vulnerabilities-Ukraine's large fiscal and quasi-fiscal deficits, its lack of resilience to external shocks, and lingering weaknesses in the financial sector. Although the program's long duration was appropriate given its focus on medium-term issues, hindsight would suggest that a shorter program would have been preferable given the country's past program performance.